2021
DOI: 10.1007/s13311-020-00932-4
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Selective MNK Inhibitor Rescues Deficits Associated with Fragile X Syndrome in Mice

Abstract: Fragile X syndrome (FXS) is the most common inherited source of intellectual disability in humans. FXS is caused by mutations that trigger epigenetic silencing of the Fmr1 gene. Loss of Fmr1 results in increased activity of the mitogen-activated protein kinase (MAPK) pathway. An important downstream consequence is activation of the mitogen-activated protein kinase interacting protein kinase (MNK). MNK phosphorylates the mRNA cap-binding protein, eukaryotic initiation factor 4E (eIF4E). Excessive phosphorylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 102 publications
(167 reference statements)
0
8
0
Order By: Relevance
“…A promising development on this aspect, comes from the work of Wei et al, who have shown that although DNA methylation patterns between brain and peripheral tissues is differential, DNA methylation levels of the Amyloid Precursor Protein (APP) gene is consistent in both tissues and is a prospective candidate for a viable AD pathogenesis biomarker [ 82 ]. The phenotypic manifestation of Fragile X syndrome (FXS) has been correlated with eIF4E phosphorylation in both human and mice patients [ 31 , 37 , 75 ] and currently, the available treatments to modulate eIF4E activity are by the usage of the anti-diabetic drug Metformin [ 28 ], the anti-cancer drug eFT508 or tomivosertib [ 74 ] among others which have unwanted side effects. Presently for treatment of FXS, efforts are being taken to induce expression of the FMR1 gene, whose repression results in the disease manifestation.…”
Section: Maternal Dietary and Supplementary Intakesmentioning
confidence: 99%
“…A promising development on this aspect, comes from the work of Wei et al, who have shown that although DNA methylation patterns between brain and peripheral tissues is differential, DNA methylation levels of the Amyloid Precursor Protein (APP) gene is consistent in both tissues and is a prospective candidate for a viable AD pathogenesis biomarker [ 82 ]. The phenotypic manifestation of Fragile X syndrome (FXS) has been correlated with eIF4E phosphorylation in both human and mice patients [ 31 , 37 , 75 ] and currently, the available treatments to modulate eIF4E activity are by the usage of the anti-diabetic drug Metformin [ 28 ], the anti-cancer drug eFT508 or tomivosertib [ 74 ] among others which have unwanted side effects. Presently for treatment of FXS, efforts are being taken to induce expression of the FMR1 gene, whose repression results in the disease manifestation.…”
Section: Maternal Dietary and Supplementary Intakesmentioning
confidence: 99%
“…Treatment with eFT508 restored hyperactive and anxiety-related behaviors, synaptic signaling, memory, and learning abnormalities, as well as aberrant social interactions. Together, these findings bring eFT508 to the forefront as a potential treatment for the FXS [161].…”
Section: Mapk Interacting Serine/threonine Kinases (Mnk)mentioning
confidence: 82%
“…Use of one of them, eFT508 (tomivosertib, Table 1 ), has revealed roles for the MNK/eIF4E pathway in the immune checkpoint 35 and some cancer models (e.g., 36 ). Interestingly, this MNK inhibitor also showed efficacy in countering neuropathic pain 37 and relieved deficits, including behavioural ones, associated with Fragile X syndrome 38 .…”
Section: Mnks the Kinases That Phosphorylate Eif4e Are Promising Drug...mentioning
confidence: 99%